2016
DOI: 10.1523/eneuro.0040-16.2016
|View full text |Cite
|
Sign up to set email alerts
|

Transition from Target to Gaze Coding in Primate Frontal Eye Field during Memory Delay and Memory–Motor Transformation

Abstract: The frontal eye fields (FEFs) participate in both working memory and sensorimotor transformations for saccades, but their role in integrating these functions through time remains unclear. Here, we tracked FEF spatial codes through time using a novel analytic method applied to the classic memory-delay saccade task. Three-dimensional recordings of head-unrestrained gaze shifts were made in two monkeys trained to make gaze shifts toward briefly flashed targets after a variable delay (450-1500 ms). A preliminary a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
118
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(129 citation statements)
references
References 91 publications
11
118
0
Order By: Relevance
“…A number of recent studies have investigated related issues, among them Sereno and Lehky (2011) and two studies by Sajad et al (2015, 2016). Sereno and Lehky have shown that population activity from area LIP allows to decode visual information at high spatial resolution.…”
Section: Methodsmentioning
confidence: 99%
“…A number of recent studies have investigated related issues, among them Sereno and Lehky (2011) and two studies by Sajad et al (2015, 2016). Sereno and Lehky have shown that population activity from area LIP allows to decode visual information at high spatial resolution.…”
Section: Methodsmentioning
confidence: 99%
“…We began this analysis by considering whether the addition of the landmark (and/or its shift) obviate the basic egocentric target-to-gaze transformation reported in our previous FEF studies (Sajad et al , 2016. Overall, we found that the T and G (in eye coordinates) models continued to dominate visual ( Supplementary Fig.…”
Section: Does the Landmark Fundamentally Alter The Fef Egocentric Tramentioning
confidence: 81%
“…Thus, one would expect any cortical signal that integrates egocentric and allocentric information to be present at this point in the system. We recently found that (in the absence of landmarks) the FEF produces a target-to-gaze coding transformation in egocentric coordinates (Sajad et al , 2016. Based on this, one might hypothesize that an allocentric influence should occur within and between these codes.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations